Intratumoral heterogeneity and genetic characteristics of prostate cancer. Issue 12 (25th March 2020) - Wu, Bo; Lu, Xin; Shen, Haibo; Yuan, Xiaobin; Wang, Xin; Yin, Nan; Sun, Libin; Shen, Pengliang; Hu, Caoyang; Jiang, Huanrong; Wang, Dongwen
Abstract : Prostate cancer is a heterogeneous disease and optimum gene targeting treatment is often impermissible. We aim to determine the intratumoral genomic heterogeneity of prostate cancer and explore candidate genes for targeted therapy. Exome sequencing was performed on 37 samples from 16 patients with prostate cancer. Somatic variant analysis, copy number variant (CNV) analysis, clonal evolution analysis and variant spectrum analysis were used to study the intratumoral genomic heterogeneity and genetic characteristics of metastatic prostate cancer. Our study confirmed the high intratumoral genetic heterogeneity of prostate cancer in many aspects, including number of shared variants, tumor mutation burden (TMB), variant genes, CNV burden, weighted genome instability index (wGII), CNV profiles, clonal evolutionary process, variant spectrum and mutational signatures. Moreover, we identified several common genetic characteristics of prostate cancer. Alterations of DNA damage repair genes, RTK/RAS pathway associated gene RASGRF1 and autophagy gene EPG5 may be involved in tumorigenesis in prostate cancer. CNV burden and DNA damage repair (DDR) genes may be associated with metastasis of prostate cancer. Abstract : What's new? Prostate cancer is a heterogeneous disease, making the development of gene targeting therapies difficult. This study confirmed the high intratumoral genetic heterogeneity of prostate cancer in the number of shared variants, tumor mutation and copy number variation (CNV) burden, weighted genome instability index, clonal evolutionary process, and variant spectrum as well as variant genes, CNV profiles, and mutational signatures. The authors could however identify several common genetic characteristics of prostate cancer. Thus, RASGRF1 and EPG5 may be involved in the tumorigenesis of prostate cancer. Furthermore, the CNV burden and DNA damage repair genes may be associated with metastatic prostate cancer.